Treading the Risks in International Management - Amol Gore; Pekka Kess (International School for Social and Business Studies, 2014)
The article presents the results of a research on students' competencies selfesteem. The research was conducted in the years 2009-2012, on a sample of 1,831 students, under the project called 'SYNERGY - MCSU Faculty of Economics students' competencies development by gaining practical knowledge.' co-financed by the European Union from the European Social Fund. The purpose of the research was to pinpoint the areas of competencies that are considered to be essential for business and determine the level of students' self-esteem in the identified areas. The main objective of the article is to show the competencies that are desirable from the business point of view, but are, in the opinion of the students, at a rather low level and require special attention and development. The paper presents the key findings of the study: the lowest self-esteem level was observed in the area of knowledge needed by the employers, the highest in the attitudes wanted by the labor market. Positive relationship was found between the level of competence self-esteem and the respondents' year of study.